Wide Complex Tachycardia in Arrhythmogenic Right Ventricular Cardiomyopathy: Electrocardiogramand Intracardiac Electrogram Features. Issue 1 (March 2022) - Nagarakanti, Rangadham; Raj, Kavin
Case of an arrhythmogenic right ventricular cardiomyopathy with associated arrhythmias discussing classical electrocardiogram and intracardiac electrogram findings.